Periodization of training load during preparatory and performance shaping phases of a 50 and 20 km race walker - Brodani, J.; Czakova, M.; Toth, M.; Pavlovi, R. (Sport Science - International Scientific Journal of Kinesiology, 2015)
Article points out special training periodization indicators during sports training and peaking performance of racewalker to 50 km and 20 km. We special focus on the period of the first peak of the season in the annual training cycle, which reached their personal best performances in a combination of both racewalker disciplines. Based on the results of the model has been created for special training indicators for racewalkers with performance to 20 km 1:21:00 hours and 50 km 3:40:0 hours.